La importancia del factor humano en la implementación de metodologías ágiles (2020)
The value of the human factor in the implementation of agile methodologies in software programming projects is analyzed, as well as its impact on their success, according to the experience of professionals in the area and an exhaustive bibliographic review on the subject . In particular, the relationship between ceremonies, tools, and human capital in companies is discussed; based on value criteria, results of surveys and interviews that allowed to conclude the type of interaction and the importance of all these resources in the different phases of a project, for a successful outcome.